Diaspora as an actor of migration policy - Agnieszka Weinar (University of Warsaw, Centre of Migration Research (CMR), 2008)
The migration and development agendas have been only recently drawn together in the context of migration policy. It has been creating .diaspora. as one of the main actors able to respond aptly to the new challenging agenda. At the same time, the traditional concept of .migrant communities. has been assigned different ontological status. To meet the ambitious goals the diaspora is being created as a political actor and it assumes characteristics of a trans-state and trans-national community to fulfil the promise of the policy agenda. The present woorking paper is the first report on the ongoing research project, which aims at studying linkages between migration policy and diaspora engagement. The report presents outcomes of the document-based analysis of the term "diaspora" as used in various policy documents.
Keywords: 330; Migranten; Auswanderung; Ethnische Gruppe; Migrationspolitik; EU-Politik; EU-Staaten